Letter from John Struthers to James Curtis Booth, November 27, 1879 - Struthers, John (1879)
John Struthers inquires about some land that James Curtis Booth (1810-1888) is selling.
Keywords: Booth, James Curtis, 1810-1888; Real property; Struthers, John